Improving the documentation and findability of data services and repositories: A review of (meta)data management approaches. (December 2022) - Řezník, Tomáš; Raes, Lieven; Stott, Andrew; De Lathouwer, Bart; Perego, Andrea; Charvát, Karel; Kafka, Štěpán
Abstract: This scientific review paper aims at challenging a common point of view on metadata as a necessary evil and something mandatory to the data creating and dataset publishing process. Metadata are instead presented as a crucial element to ensure the findability of data services and repositories. This paper describes a way through four levels of metadata management and publication, from default unstructured data, through schema-based metadata with literal values and/or URIs, towards linked open (meta)data providing explicit linkage between reliable data resources. Such research was conducted within the European Union's project PoliVisu. Special attention is given to the following: (1) guidance on publication aimed at the broad audience of search engine users and (2) the publication of geo (meta)data not only via standard technologies, such as the OGC Catalogue Service for Web and open data portals, but also through leading search engines (that are Schema.org-based). Highlights: Metadata developed in line with open linked data concept are scarce in geosciences. The presented paradigm revokes an artificial border between data and metadata. Open linked (meta)data are advertised attractively in search engines. Multiple-times more users can be attracted, both, within as well beyond geosciences. Incremental implementations approach is a novel one towards open linked (meta)data.